2007
DOI: 10.4049/jimmunol.178.1.271
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Produced by Dendritic Cells from Lupus-Prone Mice Inhibits CD4+CD25+ T Cell Regulatory Functions

Abstract: The B6.Sle1.Sle2.Sle3 triple congenic mouse (B6.TC) is a model of lupus coexpressing the three major NZM2410-derived susceptibility loci on a C57BL/6 background. B6.TC mice produce high titers of antinuclear nephrogenic autoantibodies and a highly penetrant glomerulonephritis. Previous studies have shown the Sle1 locus is associated with a reduced number of regulatory T cells (Treg) and that Sle3 results in intrinsic defects of myeloid cells that hyperactivate T cells. In this report, we show that B6.TC dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(193 citation statements)
references
References 51 publications
(62 reference statements)
12
181
0
Order By: Relevance
“…60 Furthermore, T REG cell suppressive functions are reduced in SLE patients and MRL mice, and it is thought that this is due to elevated levels of IL-6, which inhibits T REG cell function. 42,94,95 T REG cells have significantly higher expression of HSP90 than T cells. The high expression of HSP90 in T REG suggests a role for HSP90 in FoxP3 expression and may explain why we found higher levels of FoxP3 2 CD3 1 CD8 1 T cells.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 89%
“…60 Furthermore, T REG cell suppressive functions are reduced in SLE patients and MRL mice, and it is thought that this is due to elevated levels of IL-6, which inhibits T REG cell function. 42,94,95 T REG cells have significantly higher expression of HSP90 than T cells. The high expression of HSP90 in T REG suggests a role for HSP90 in FoxP3 expression and may explain why we found higher levels of FoxP3 2 CD3 1 CD8 1 T cells.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 89%
“…This process could be driven to affinity maturation and isotype class switching by antigen and TLR-dependent signals or by nonspecific activation of DC and hypersecretion of cytokines, such as IL-6. DC from autoimmune B6.Sle1.-Sle2.Sle3 congenic mice have also been shown to suppress Treg cell function in vitro via IL-6 [55]. It is tempting to explain the complexity of human lupus in terms of cumulative effects on antigen-specific and antigen-independent regulation of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…These studies provided thus a plausible explanation for the systemic nature of the disease. A lack of Treg-mediated immune regulation in lupus is now a general consensus, although there have been differences in the findings as to whether a reduced Treg frequency [40-46, 49-53, 58-61, 68, 71-75, 82-84, 88, 90], defective Treg functions [44,48,53,57,59,60,66,70,76,80,89,90] or both, or alternatively an insensitivity of the Treg target cells [66,67,70,89,99], are truly accountable. By using CD25 as the marker, an early study by Crispin and colleagues first showed that, in lupus patients with active disease, the frequencies of Treg (CD4+CD25 +/bright ) were significantly decreased, while T cells with an activated T helper (Th) effector phenotype (CD4 + CD69 + ) increased [40].…”
Section: Aberrant Treg Frequencies and Functions Associated With Lupumentioning
confidence: 99%
“…However, there have also been controversial findings from other studies showing that the frequency of Treg cells, either defined as CD4 + CD25 bright or CD4 + Foxp3 + , could be normal www.intechopen.com [48,66,67,70,85,86] or even increased [47, 54-56, 58, 62-65, 69, 74, 76-79, 81] in lupus disease. Instead, some of these studies suggested that Treg were functionally defective and less capable of suppressing those potentially auto-reactive lymphocytes in lupus patients [44,48,53,57,59,60,66,76,80], and the mouse models [70,89,90]. Again, alternative findings demonstrating lupus Treg being functionally normal [49,50,62,67,85], or at least normal in majority of patients tested [48,64], or even enhanced in some way [68,80,87] added further confusion as well as interest to the matter.…”
Section: Aberrant Treg Frequencies and Functions Associated With Lupumentioning
confidence: 99%
See 1 more Smart Citation